Ir/PTC cooperatively catalyzed asymmetric umpolung allylation of α-imino ester enabled synthesis of α-quaternary amino acid derivatives bearing two vicinal stereocenters. Issue 12 (25th January 2017) - Su, Yong-Liang; Li, Yu-Hui; Chen, Yu-Gen; Han, Zhi-Yong
Abstract : A novel Ir/PTC (phase-transfer catalyst) cooperatively catalyzed asymmetric umpolung allylation of simple α-imino esters is developed and it provides facile access to α-quaternary amino acid derivatives bearing two vicinal stereocenters. Abstract : A novel Ir/PTC (phase-transfer catalyst) cooperatively catalyzed asymmetric umpolung allylation of simple α-imino esters is developed and it provides facile access to α-quaternary amino acid derivatives bearing two vicinal stereocenters. Both the metal catalyst and the phase-transfer catalyst are crucial for this methodology. The reaction features good yields, high diastereo- and enantio-selectivities, ease of scale-up to gram scale and further transformation of the products ( e.g. to quaternary proline analogues with multi stereocenters).